For ethical 'impactology'. Issue 1 (2nd January 2019) - Donovan, Claire
ABSTRACT: The routine evaluation of broader impacts of research has made the UK an impact-aware culture, although the practice of assessment has run ahead of its theory. The paper describes UK practice in assessing broader impacts, notes the rise of the profession of 'impactology' alongside the rise of academics' impact-fatigue, and notes that the two combined may lead us to commit 'metricide' by abandoning time-consuming impact narratives in favour of simple metrics. The paper concludes by considering what an ethical impactology might look like, and finds at its heart the responsible use and non-use of metrics.